Effect of cover cropping and biosolarization on eggplant growth, soil pests, and soil nitrogenDryad - Shayne Morrissey; Natalie Chueh; Carolina Conte; Christopher Simmons (Journal of Agriculture and Food Research, 2025)
Cover cropping and biosolarization are agricultural practices capable of controlling soil pests, enhancing soil health, and improving crop yields. Biosolarization utilizes solar heating and biochemical pesticide production from organic matter amendments to control agricultural pests. This study evaluates the effects of using cover crop residues from Brassica juncea monocultures and mixtures with Vicia villosa as biosolarization amendments on subsequent eggplant production, soil nitrogen, and soil pests, including weeds and fungal crown rot. These treatments were compared to non-biosolarized soil amended with the same cover crop monocultures and mixtures, non-amended soil treated with solarization, and non-amended, untreated soil controls. Results indicate the cover crop amendments improve eggplant fruit yield by 154 %, while decreasing fungal crown rot disease relative to untreated controls (P < 0.05). Additionally, employing biosolarization with these amendments reduced subsequent weed mass relative to cover cropped, solarized, and untreated controls (P < 0.05). Biosolarization also increased soil nitrate concentrations compared to cover crop-amended soil without biosolarization (P < 0.05). These findings exhibit the additive potential of cover cropping and biosolarization practices to be implemented in agriculture to control soil pests without chemical fumigants, while enhancing soil health and crop productivity.